2020
DOI: 10.1002/admi.202001102
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Black Phosphorus and Strategies to Enhance Its Ambient Lifetime

Abstract: water resulting in rapid decomposition, [12] making processing of the material challenging and resulting in detrimental effects on its optical and electronic properties. [13] The ambient degradation of BP presents a significant hurdle to realizing the full potential of BP in various applications. The successful application of BP will rely either on its exclusion from the factors that contribute to its degradation or protection methods that prevent its degradation in ambient conditions. Literature reports that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 105 publications
(243 reference statements)
0
28
1
1
Order By: Relevance
“…and 𝐵 2𝑔 vibrational modes have all been identified as signatures of the oxidation and degradation, as well as a shift in the peak position. [23,26,27,29,34,50,60,61] However, in our analysis (data not shown), we do not see a clear Raman signature for degradation in our samples, suggesting that Raman spectroscopy may not be the best tool to characterize the BP degradation. Therefore, we evaluate the environmental stability by AFM, as previous works have shown that the oxidation increases the BP surface roughness [31,50] and crystal volume.…”
contrasting
confidence: 57%
See 2 more Smart Citations
“…and 𝐵 2𝑔 vibrational modes have all been identified as signatures of the oxidation and degradation, as well as a shift in the peak position. [23,26,27,29,34,50,60,61] However, in our analysis (data not shown), we do not see a clear Raman signature for degradation in our samples, suggesting that Raman spectroscopy may not be the best tool to characterize the BP degradation. Therefore, we evaluate the environmental stability by AFM, as previous works have shown that the oxidation increases the BP surface roughness [31,50] and crystal volume.…”
contrasting
confidence: 57%
“…The elemental P peaks can be observed at ̴ 130 eV, [65] while the peak ̴ 135 eV is attributed to oxides species (P-O), where P2O5 is suggested to be the most stable form. [29] The broad peak around ̴ 127 eV originates from the s photoelectron Si satellite from the substrate. [22] For the control sample, we can observe a relative decrease in intensity of the elemental P peaks, followed by an increase in the relative amount of oxides species.…”
Section: Raman Spectroscopy Has Been Extensively Used To Study Defect...mentioning
confidence: 99%
See 1 more Smart Citation
“… 1 3 However, the material is unsuitable for electronic and optoelectronic applications due to a lack of stability in the ambient environment. 4 Some of the engineering approaches like encapsulation, 5 pulsed laser exfoliation, 6 solvent passivation, 7 and oxygen plasma etching 8 have guided to make the material stable. The methods, however, are not very promising for long-term stability, which is a real challenge in terms of material growth, device processing, and packaging for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…[15] With water involved, the oxidization process becomes much more complex, and the precise roles of water, oxygen, and light are still unclear and in active debate with different mechanisms, such as the oxidization behaviors that took place in water solvent and moisture atmosphere result in different degradation products. [16][17][18][19][20] One of the oxidization mechanisms is reported that the water molecular (humidity) exhibits catalyzed function that first lowers the reaction energy between BP and oxygen, [12] and then reacts with phosphorus oxides forming phosphorus acid, which accelerates the oxidization and etching speed. [11,12,21] An alternative mechanism was proposed by Hu et al, who revealed the BP oxidization occurred even in the dark environment with the coexistence of water and oxygen, which was attributed to the polarization effect of water that lowers the energy level of oxygen, resulting in acceleration of electron transfer from BP to oxygen that triggers BP oxidization.…”
mentioning
confidence: 99%